Achieving competitive advantage through innovativeness - Pavlina, Jasmina; Černe, Matej (Univerzita Pardubice, 2010)
Innovativeness is becoming an increasingly important factor in the development of company’s competitive advantage. The purpose of this article is to present the role played by innovativeness in Slovenian companies. To this end, we conducted a survey on 68 medium and large Slovenian companies. The results showed that both means of enhancing innovativeness, investments in innovation and promoting employee innovativeness, lead to improved competitive advantage of Slovenian companies.
Keywords: innovativeness; competitive advantage; promoting employee innovativeness; investments in innovation